Transformation of Male Domination Patterns in the Wahdah Islamiyah Movement: From Domination to Partnership-Controlled - Ismah Tita Ruslin,; Syarifuddin Jurdi,; Nurul Khatimah Armanto, (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2025)
This study examines gender relations within Wahdah Islamiyah, focusing on transforming patriarchal patterns. It explores alternative perspectives on women’s presence in public spaces, which are influenced by women’s awareness through strategies for utilizing resources, ideas, and capacities, in addition to external demands. Qualitative methods with case studies, theories of agency, and organizational change ‘isomorphism’ are employed to construct arguments by conducting a thorough examination of the context, process, and significance of the unit being examined. There are three phases to the investigation of the Wahdah Islamiyah movement, which is examined both before and following its transformation into an organization. Firstly, the initial phase of the 1980s was characterized by an exclusive pattern of domination. Secondly, a restricted adaptive pattern that developed during the expansion of da’wah to the public sphere in the 1990s. Thirdly, the controlled partnership pattern, which commences with the institutional transformation of Muslimah Wahdah in 2005 and is immediately followed by the strengthening of Muslimah’s negotiating position following the third congress in 2016. Transforming patriarchal patterns, which can be perceived as a negotiation of patriarchy, are shaped by external environmental factors and the presence of women’s agencies.